Pharmacological activation of the p53 pathway by nutlin-3 exerts anti-tumoral effects in medulloblastomas - Künkele, Annette (Oxford University Press, 2012)
Medulloblastomas account for 20% of pediatric brain tumors. With an overall survival of 40%–70%, their treatment is still a challenge. The majority of medulloblastomas lack p53 mutations, but even in cancers retaining wild-type p53, the tumor surveillance function of p53 is inhibited by the oncoprotein MDM2. Deregulation of the MDM2/p53 balance leads to malignant transformation. Here, we analyzed MDM2 mRNA and protein expression in primary medulloblastomas and normal cerebellum and assessed the mutational status of p53 and MDM2 expression in 6 medulloblastoma cell lines. MDM2 expression was elevated in medulloblastomas, compared with cerebellum. Four of 6 medulloblastoma cell lines expressed wild-type p53 and high levels of MDM2. The tumor-promoting p53-MDM2 interaction can be inhibited by the small molecule, nutlin-3, restoring p53 function. Targeting the p53-MDM2 axis using nutlin-3 significantly reduced cell viability and induced either cell cycle arrest or apoptosis and expression of the p53 target gene p21 in these 4 cell lines. In contrast, DAOY and UW-228 cells harboring TP53 mutations were almost unaffected by nutlin-3 treatment. MDM2 knockdown in medulloblastoma cells by siRNA mimicked nutlin-3 treatment, whereas expression of dominant negative p53 abrogated nutlin-3 effects. Oral nutlin-3 treatment of mice with established medulloblastoma xenografts inhibited tumor growth and significantly increased survival. Thus, nutlin-3 reduced medulloblastoma cell viability in vitro and in vivo by re-activating p53 function. We suggest that inhibition of the MDM2-p53 interaction with nutlin-3 is a promising therapeutic option for medulloblastomas with functional p53 that should be further evaluated in clinical trials.